Kompetensi Guru Pendidikan Agama Islam dalam Mengelola Kelas dan Mengatasi Kesulitan Belajar Peserta Didik di SMA NU Juntinyuat Indramayu - Arwani Arwani; Aang Kunaefi (Fakultas Pendidikan IAI Pangeran Dharma Indramayu, 2026)
The competence of Islamic religious education teachers is one of the mandatory competencies for every educator. A competent teacher is one who possesses four competencies: pedagogical, personality, social, and professional. In this context, teachers are expected to be able to address issues that arise during the Islamic religious education learning process, such as classroom management and overcoming student learning difficulties. Based on a preliminary study, some Islamic religious education teachers still lack the ability to apply these competencies. Therefore, the author addressed the following issues: How are Islamic religious education teachers competent in managing classes at SMA NU Juntinyuat Indramayu? And how are Islamic religious education teachers competent in overcoming student learning difficulties at SMA NU Juntinyuat Indramayu? This research is a descriptive qualitative study using a field survey approach (field research). Data collection techniques used interviews and documentation. Data analysis was conducted inductively using an interactive model, including data collection, data reduction, data presentation, and data conclusions. The results of this study indicate that: First, Islamic religious education teachers are competent in managing classes. Second, Islamic religious education teachers are competent in overcoming student learning difficulties.